2019
DOI: 10.2217/epi-2018-0218
|View full text |Cite
|
Sign up to set email alerts
|

Role of BCYRN1 in hepatocellular carcinoma pathogenesis by lncRNA–miRNA–mRNA network analysis and its diagnostic and prognostic value

Abstract: Aim: This study aimed to excavate the roles of BCYRN1 in hepatocellular carcinoma (HCC). Methods: A comprehensive strategy of microarray data mining, computational biology and experimental verification were adopted to assess the clinical significance of BCYRN1 and identify related pathways. Results: BCYRN1 was upregulated in HCC and its expression was positively associated with both tumor, node, metastasis and worse survival rate in patients with HCC. Through combing plasma BCYRN1 with alpha fetoprotein, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…The authors analyzed BCYRN1 expression in plasma from 124 HCC patients, 79 cirrhosis patients, 68 hepatitis B patients and 74 healthy controls. Plasma BCYRN1 expression of HCC patients was significantly higher than that of healthy controls (p < 0.001) or hepatitis B patients (p < 0.01) [159]. Furthermore, combined detection of BCYRN1 and AFP improved the diagnosis of HCC in their cohort.…”
Section: Potential Diagnostic Biomarkers In Hccmentioning
confidence: 89%
See 2 more Smart Citations
“…The authors analyzed BCYRN1 expression in plasma from 124 HCC patients, 79 cirrhosis patients, 68 hepatitis B patients and 74 healthy controls. Plasma BCYRN1 expression of HCC patients was significantly higher than that of healthy controls (p < 0.001) or hepatitis B patients (p < 0.01) [159]. Furthermore, combined detection of BCYRN1 and AFP improved the diagnosis of HCC in their cohort.…”
Section: Potential Diagnostic Biomarkers In Hccmentioning
confidence: 89%
“…These results suggested the potential that ncRNAs that act as ceRNAs and their associated ceRNETs may be useful for clinical applications as diagnostic biomarkers of HCC (Table 5). Ming et al demonstrated that the lncRNA BCYRN1 functions as a ceRNA to play a vital role in HCC [159]. The authors analyzed BCYRN1 expression in plasma from 124 HCC patients, 79 cirrhosis patients, 68 hepatitis B patients and 74 healthy controls.…”
Section: Potential Diagnostic Biomarkers In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…And research from Ren et al found that overexpression of BCYRN1 facilitated tumor progression and up-regulated EpCAM expression in gastric carcinoma [10]. Furthermore, BCYRN1 has been illustrated to be greatly expressed in HCC and its expression was actively connected with tumor-node-metastasis and unfavorable prognosis in HCC patients [11]. However, study on the potential molecular mechanisms of BCYRN1 in HCC was scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidences indicate that the aberrant expression of lncRNAs, developing into a highly active research hotspot, plays significant roles in tumorigenesis and acts as novel molecular biomarkers for the diagnosis and prognosis of HCC. More recently, a growing body of research shows that the construction of the ceRNA network reveals its diagnostic and prognostic value in HCC by comprehensive analysis [14][15][16][17]. For example, lncRNA SSTR5-AS1, acting as a ceRNA, sponge mir-15b-5p to regulate carbonic anhydrase 2 (CA2) function in the progression of hepatitis B virusrelated hepatocellular carcinoma [18].…”
Section: Discussionmentioning
confidence: 99%